Comprehensive Evaluation of Anterior Corneal Change in Asphericity Calculated by the Tangential Radius of Curvature after LASIK - Jinglu Ying; Jianqiu Cai; Leru Zhu; Yi Zha (Journal of Ophthalmology)
To evaluate the change in the anterior corneal asphericity (ΔQ) comprehensively calculated using the tangential radius (rt) after LASIK. Forty-two right eyes were evaluated using the Orbscan II corneal topographer. The pre- and postoperative Q-values of the flat principal semimeridians calculated by the sagittal radius were compared to those by the tangential radius. The Q-value of each semimeridian in the horizontal region was calculated by rt. Fourier fitting was used to model the 360-semimeridional variation of Q-values and to fit the Q-values in the vertical region before and after surgery. There were significant differences in Q-values between the two methods before (P<0.001) and after surgery (P=0.003). A significant increase in postoperative Q-value was detected compared to preoperative Q-value (P<0.001) calculated by rt. The 360-semimeridional variation of the Q-values was well fitted with a third- and fourth-degree Fourier function before and after surgery. The ΔQ-value distribution presented double valley variation, with the amount of ΔQ being lowest in the near-vertical regions and highest in the near-horizontal regions. Calculating the Q-value with rt combined with Fourier fitting, we evaluated 360 ΔQ-values’ variation of semimeridians of the entire anterior corneal surface and then displayed true and complete anterior corneal shape after LASIK.